Case-based learning practices for enhancing cognitive learning outcomes and computational thinking in teacher education - Ardiansyah, Roy; Atmojo, Idam Ragil Widianto; Subandi, Ira Wati; Matsuri, Matsuri; Adi, Fadhil Purnama; Saputri, Dwi Yuniasih (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
The objective of this research is to determine the effect of the case-based learning model on students' cognitive learning outcomes and computational thinking skills. This is a quantitative study. The sample was selected using cluster random sampling techniques. Data collection was carried out using essay tests to measure cognitive learning outcomes and computational thinking, as well as scales to assess students' enjoyment of learning. Validity and Data analysis were performed using PLS-SEM. The results of this study are as follows. The findings indicate a positive effect of the case-based learning model on the cognitive learning outcomes of PGSD UNS students. There is a significant effect of students' computational thinking on their cognitive learning outcomes. Based on these results, it can be concluded that the case-based learning model affects students' cognitive learning outcomes. Then there is a significant effect of case-based learning on computational thinking. The results of this research can be used as a reference for further research.